Assessing the Participation of Students with Intellectual Impairment in Extracurricular Activities in Primary Schools in Dar es Salaam City Council in Tanzania - Baraka Baltazar; Georgina Mugisha (PT. Pusmedia Group Indonesia, 2026)
This study examined the participation of pupils with mild and moderate intellectual impairment in extracurricular activities in public primary schools within Dar es Salaam City Council. A qualitative approach was employed to identify the types of inclusive extracurricular activities, explore strategies promoting student participation, and assess barriers faced by teachers and administrators. Data were collected through interviews, observations, and document review, and the study was guided by Bronfenbrenner’s Ecological Systems Theory, which highlights the influence of family, policy, and society. Participants included an education officer, school administrators, special needs teachers, and pupils with intellectual impairment, selected through purposive and random sampling to ensure rich information. Thematic analysis of the collected data revealed that, although schools offered diverse extracurricular activities and applied various inclusion strategies, participation among pupils with mild and moderate intellectual impairment remained low due to limited resources, inadequate teacher training, insufficient assistive tools, and persistent social barriers. Strengthening inclusive support systems is essential to ensure extracurricular opportunities effectively meet these students’ needs. Key recommendations include enhancing teacher capacity, improving access to assistive resources, adapting school infrastructure, and raising community awareness to promote meaningful and equitable participation in extracurricular activities.